Two Eocene species of Culiseta (Diptera: Culicidae) from the Kishenehn Formation in Montana - Harbach, Ralph E.; Greenwalt, Dale (Zootaxa, 2012)
Culiseta kishenehn, sp. n. and Cs. lemniscata, sp. n. (Diptera: Culicidae: Culisetini) are described from compression fos-sils from the 46 million year old Kishenehn shale deposits in Montana, USA. The new species appear to share featureswith extant species of subgenera Climacura and Culicella, respectively. The antiquity of Culiseta is examined and previ-ously described Eocene fossil species are discussed. Eoaedes gen. n. and Aetheapnomyia gen. n. are established for Aedes damzeni Podėnas and Ae. hoffeinsorum Szadziewski, two Eocene fossil species in Baltic amber.